Analysis of Sterol Glucosides in Momordica charantia L. Extracts and Nutraceutical Products: Analysis of Sterol Glucosides - Muhamad, Musthahimah; Yan Choo, Chee; Imbuh Ngilah, Emmelly; Gundadon, Hendrynus; Tsan, Fui Ying; Hitotsuyanagi, Yukio (Iranian Journal of Pharmaceutical Sciences, 2021)
Sterol glucosides were biosynthesised in Momordica charantia L. and used as markers for the standardization of M. charantia extracts. The sterol glucoside, charantin, used as a marker consisted of equal amounts of two sterol glucosides, namely, 5, 25-stigmastadienol glucoside (1) and β-sitosterol glucoside (2). Most quantitation methods either mixed up both isomers, namely (1) and stigmasterol glucoside (3) or both the sterol glucosides (1) and (2) were not separated in the quantitation methods. The labelling of individual sterol glucosides needs to be clearly stated in nutraceutical products. This study aimed to resolve the separation of the commonly mixed-up sterol glucosides and further validate a high-performance liquid chromatography-photodiode array detector (HPLC-PDA) method for the quantification of individual sterol glucosides in M. charantia. The HPLC-PDA instrument was used for method development as it is a universal instrument available in most nutraceutical companies. Sterol glucosides (1)-(3) were separated with a Zorbax SB-C18 column and an isocratic HPLC mobile phase system of 88% methanol in deionized water. The wavelength of the PDA detector was set at 200 to 500 nm with a linearity range of 90 to 300 μg/mL and a good correlation coefficient of r2 > 0.99. The validated method was applied to fresh fruits and nutraceutical products. The sterol glucoside (1) is the major constituent in charantin. Hybrid fruits biosynthesised higher content of sterol glucosides compared to non-hybrid fruits. The content of (1)-(3) in the final nutraceutical products fluctuates and dependent on the source of raw material. Thus, standardization of extracts is essential in nutraceutical production to ensure uniform content of secondary metabolites and reproducible therapeutic effect.